2017
DOI: 10.1007/s11136-017-1715-1
|View full text |Cite
|
Sign up to set email alerts
|

The association between somatic and psychological discomfort and health-related quality of life according to the elderly and non-elderly

Abstract: Our study suggests that somatic and psychological discomfort symptoms are associated with HRQOL. The main factors related to HRQOL vary according to age and large prospective studies and clinical trials are needed to clarify the association between specific symptoms and HRQOL according to the age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Third, Tobit models and ordinal logit models were used to investigate the association between poverty and HRQOL. Although the EQ-5D-3 L includes only five items and is not perfectly comparable with other comprehensive instruments on mental disorders, one study revealed that somatic and psychological symptoms are related to the EQ-5D-3 L [44]. Thus, the EQ-5D-3 L can aid in screening mental disorders [45].…”
Section: Discussionmentioning
confidence: 99%
“…Third, Tobit models and ordinal logit models were used to investigate the association between poverty and HRQOL. Although the EQ-5D-3 L includes only five items and is not perfectly comparable with other comprehensive instruments on mental disorders, one study revealed that somatic and psychological symptoms are related to the EQ-5D-3 L [44]. Thus, the EQ-5D-3 L can aid in screening mental disorders [45].…”
Section: Discussionmentioning
confidence: 99%
“…Elders report greater levels of pain intensity as compared to younger ones ( Nahin, 2015 ). Pain is one of the most widely cited symptoms underlying disability among older adults ( Patel et al, 2013 ), impacting their quality of life ( Lee H. S. et al, 2018 ). With aging, chronic pain experience is associated with higher risk for depression ( Turk et al, 1995 ; McCarthy et al, 2009 ; Bauer et al, 2016 ), accelerating decline in physical function and increase in the number of comorbid symptoms ( Okabe et al, 2017 ), including precipitated memory decline and increased probability of dementia ( Whitlock et al, 2017 ).…”
Section: Where Does the Systemic Chronic Inflammation Come From And Who Could Have It?mentioning
confidence: 99%
“…Psychological health involves the cognitive and emotional status of individuals, including personal beliefs, spiritual and religious meanings of life and attitudes toward suffering (Gomez et al, 2010;Lee et al, 2017). It manifests through positive feelings, thinking, learning, memory, concentration, self-esteem, bodily image and appearance, spirituality, religion and negative feelings (WHO, 1996).…”
Section: Quality Of Life Of the Elderlymentioning
confidence: 99%